Waist-hip ratio related genetic loci are associated with risk of impaired fasting glucose in Chinese children: a case control study - Song, Q. Y.; Meng, X. R.; Hinney, A.; Song, J. Y.; Huang, T.; J. Ma; Wang, H. J. (Nutr Metab (Lond)Nutr Metab (Lond)Nutr Metab (Lond), 2018)
Background: The meta-analyses of genome-wide association studies identified several waist-hip ratio (WHR) related loci in individuals of European ancestry. Since the pattern of fat distribution and the relationship between fat distribution and glucose metabolism disturbance in Chinese are different from those in Europeans, the present study aimed to explore the individual and cumulative effects of WHR-related loci on glycemic phenotypes in Chinese children. Methods: A total of 2030 children were recruited from two independent studies. Eleven single nucleotide polymorphisms (SNPs) were selected and genotyped using matrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS). Logistic regression and linear regression model were used to examine the association of 11 SNPs and genetic risk score (GRS) with impaired fasting glucose (IFG) and fasting plasma glucose (FPG), respectively. Results: Three SNPs (rs6795735, rs984222 and rs1011731) were nominally associated with IFG (all P < 0.05). Each WHR-increasing (C) allele of rs6795735 (ADAMTS9) was associated with a 40.1% increased risk of IFG (OR = 1.401, 95% CI = 1.131-1.735, P = 0.002), which remained significant after Bonferroni correction. We observed no association of both weighted and unweighted GRS with FPG and IFG (all P > 0.05). Conclusions: We identified individual effects of rs6795735 (ADAMTS9), rs984222 (TBX15-WARS2), and rs1011731 (DNM3-PIGC) on glycemic phenotypes in Chinese children for the first time. The study suggests that genetic predisposition to central obesity is associated with impaired fasting glucose, providing more evidence for the pathogenesis of diabetes.